2020
DOI: 10.1002/ana.25906
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Nucleus Deep Brain Stimulation Modulates 2 Distinct Neurocircuits

Abstract: Objective: Current understanding of the neuromodulatory effects of deep brain stimulation (DBS) on large-scale brain networks remains elusive, largely due to the lack of techniques that can reveal DBS-induced activity at the whole-brain level. Using a novel 3T magnetic resonance imaging (MRI)-compatible stimulator, we investigated whole-brain effects of subthalamic nucleus (STN) stimulation in patients with Parkinson disease. Methods: Fourteen patients received STN-DBS treatment and participated in a block-des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 44 publications
(78 reference statements)
4
55
0
Order By: Relevance
“…Changes in the regional brain volume can alter electrode targeting, reflect postoperative progression of subclinical dementia, or directly interfere with the therapeutic action of DBS [25]. Magnetic resonance imaging (MRI) is a noninvasive method that has been used to investigate structural and functional changes in PD [26][27][28][29] and predict motor outcomes following DBS based on thalamic and ventricular volumes [25]. However, few studies have focused on the relationship between STN volume and PD symptoms before and after DBS.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the regional brain volume can alter electrode targeting, reflect postoperative progression of subclinical dementia, or directly interfere with the therapeutic action of DBS [25]. Magnetic resonance imaging (MRI) is a noninvasive method that has been used to investigate structural and functional changes in PD [26][27][28][29] and predict motor outcomes following DBS based on thalamic and ventricular volumes [25]. However, few studies have focused on the relationship between STN volume and PD symptoms before and after DBS.…”
Section: Introductionmentioning
confidence: 99%
“…While some of the aforementioned studies agreed on the critical role of the same fiber bundle published as a three-dimensional dataset (1,28,29,(32)(33)(34), others revealed seeming heterogeneity about which pathway would be critical to modulate for successful DBS in OCD. Namely, the study by J o u r n a l P r e -p r o o f Liebrand et al suggested that the MFB, connecting the PFC with the ventral tegmental area, would be associated with a beneficial response (26) whereas other studies highlighted streamlines within the ALIC as being critical for OCD-DBS (28,32,42). Conventionally, the MFB is a transhypothalamic structure that does not traverse the ALIC (20,21) -and seen in this light, the studies would imply a conflicting finding.…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…DBS for movement disorders applies fairly standardized stimulation parameters, consisting of a frequency of 130 Hz, pulse widths <300 µs and variable amplitudes. Recently, burst stimulation has been developed, and this stimulation design applies the natural frequency of the targeted area, e.g., 6 Hz at the ACC, 20 Hz at the DLPFC, 4-8 Hz at the somatosensory and auditory cortex. Thus, effective outcomes can only be expected if both the target and stimulation design match.…”
Section: Toward Deep Brain Stimulation Targets and Stimulation Designs For Depressionmentioning
confidence: 99%